Impact of aggregated model-based optimization for wind farm and electric vehicle on power system stability. (January 2023) - Bhukya, Jawaharlal; Singh, Neeraj kumar; Mahajan, Vasundhara
Highlights: This paper studies the stability issues of the aggregated model of Wind Farm (WFs) and charging stations. It results in undesirable operation and malfunction in the system to cause instability. To avoid stability issues and enhance stability, the test system has been carried out by incorporated stabilizer and compensator and different combinations under various operational conditions. The rotor speed deviation is the objective function for particle swarm optimization and is formulated based on the transient stability analysis. The stability is conducted by creating a 3-ϕ fault. From the results, it is also noticed that oscillations in the system are minimized, damping in the system is enhanced, transient stability is enhanced and also the capability of aggregated model for EVs and WFs under extreme disturbances is intensified by optimizing the coordinated controllers' parameters. The effectiveness and robustness of the proposed approaches are verified on the IEEE-11 bus test system. Abstract: This paper analyses an aggregated battery charging model for Electric Vehicles (EVs) and Wind Farms (WFs). The effects of EVs and WFs on stability have become a substantial problem with comprehensive apprehension due to the intermittence power flow and irregular battery-charging behaviour. It results in undesirable operation and malfunction in the system to cause instability. In this work, it is integrated with various controllers to enhance the stability. The rotor speed deviation has been considered an objective function with various constraints for particle swarm optimization to provide the controller's optimized value and combination. It also studies the influence of transient stability problems using time-domain simulation. From stability analysis, coordinated controllers intensify the capability of SGs and WF under extreme disturbances. The effectiveness and robustness of the proposed approaches have been verified using the IEEE-11 bus test system. Graphical abstract: Image, graphical abstract